Assessing the cushioning effect of tax-benefit policies in the Andean region during the COVID-19 pandemic - Andrés Avellaneda; Rodrigo Chang; Diego Collado; H. Xavier Jara; Andrés Mideros; Lourdes Montesdeoca; David Rodríguez; Javier Torres; Omar Vanegas (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2021)
This paper aims to assess the role of tax-benefit policies in mitigating the effects of the COVID-19 crisis on the distribution of household disposable income in Colombia, Ecuador and Peru. Tax-benefit microsimulation and nowcasting techniques are used to adjust 2019 microdata to reflect the labour market and earnings situation observed in official labour force surveys collected during the pandemic. Our results show a sharp drop in household disposable income and a dramatic increase in poverty and inequality during the second quarter of 2020, with the national poverty headcount increasing by 73% in Colombia and more than doubling in Ecuador and Peru. By the end of 2020, the economy recovers but poverty and inequality remain above the pre-pandemic levels. COVID-related policies cushion the effect of the crisis at the bottom of the distribution, and their effect on poverty and inequality largely depends on the generosity of the benefits implemented. By contrast, automatic stabilisers mitigate the impact of the income shock at the top of the distribution due to the effect of social insurance contributions and personal income tax, whereas social assistance programmes in place before the pandemic fail to act as automatic stabilisers due to their design as proxy means-tested benefits.
Keywords: 330; Health; Labour Market; Income Dynamics; Microsimulation; Poverty; Covid-19; Taxation; Welfare Benefits; Economics; Public Policy